Quantifying Importance of Macrobenthos for Benthic‐Pelagic Coupling in a Temperate Coastal Shelf Sea. Issue 10 (18th October 2021) - Zhang, Wenyan; Neumann, Andreas; Daewel, Ute; Wirtz, Kai; van Beusekom, Justus E. E.; Eisele, Annika; Ma, Mengyao; Schrum, Corinna
Abstract: Benthic oxygen fluxes consist mostly of advective and diffusive terms. Both terms in the German Bight exhibit a prominent annual cycle but with opposite variation patterns. To understand the driving mechanisms quantitatively, a novel 3‐D benthic‐pelagic coupled model resolving interactions among macrobenthos, bioturbation, oxygen consumption, and carbon early diagenesis was applied to reconstruct the benthic states. Simulation results show a satisfactory agreement with field data and reveal that the benthic oxygen flux is determined by not only pelagic drivers but also by internal dynamics associated with the interaction between organic carbon and macrobenthos, and bedform morphodynamics. Variation of advective flux, characterized by summer‐low and winter‐high, is mainly driven by hydrodynamics and bedform morphodynamics, while variation of diffusive flux, featured by summer‐high and winter‐low, is a compound effect of pelagic and benthic drivers with a dominant control by macrobenthos through bioturbation. The role of bioturbation in benthic oxygen consumption is twofold: (a) on the one hand, it alters the particulate organic carbon (POC) distribution in surface sediments, thereby changing the availability of POC to oxygen consumption; (b) on the other hand, it mixes oxygen down into sediments, thereby facilitating oxygen consumption. Our results indicate that the first role prevails in sandy seafloor characterized by energetic hydrodynamics, while the second role becomes increasingly important along with a weakening of bottom currents. We found that bioturbation contributes up to 87% ± 4% and 55% ± 8% of the total benthic oxygen fluxes in muddy seabed and at a regional scale (the German Bight), respectively. Plain Language Summary: Oxygen is important to sustain life and to regulate carbon cycling in our Earth system. However, because of global warming, there is growing concern that oxygen in the ocean is declining, partly due to temperature increase and partly due to nutrient enrichment that leads to excessive production of organic carbon which consumes oxygen during its degradation. To mitigate this potential threat, it is important to understand the mechanisms that control oxygen consumption near and at the seafloor. To this end, our study provides a quantitative assessment of the driving factors for oxygen consumption across the sediment‐water interface in a coastal sea. We found that animals living in the seafloor are of vital importance in controlling oxygen consumption in sediments. Therefore, it is important for us to protect benthic life and biodiversity, which in turn helps to mitigate the impact on (marine) ecosystems. Key Points: A novel 3D numerical model resolves interactions among macrobenthos, bioturbation, oxygen consumption, and carbon early diagenesis The role of bioturbation in benthic oxygen consumption is twofold and dependent on sediment properties and hydrodynamics Bioturbation‐induced oxygen transport contributes to more than half of the total benthic oxygen fluxes in the German Bight